"Question17
Show that : 1 - sin60°/cos60° = tan60°-1/tan60° + 1
Chapter6,T-Ratios of particular angles Exercise -6 ,Page number 288"
Answers
Answered by
2
Hey there!
We know that,
sin60 = √3/2
cos60 = 1/2
tan60 = √3
Now,
Finding the value of L. H. S,
1 - sin60/ ( cos60 )
=[ 1 - √3/2 ] / 1/2
= [ 2 - √3 / 2 ] * 2
= 2 - √3
Now, Finding Value of R. H. S,
tan60 - 1 / tan60 + 1
= √3 - 1 / √3 + 1 [ Rationalise denominator ]
= (√3 - 1 )² / 2
= 3 + 1 - 2√3 /2
= 4 - 2√3 /2
= 2 [ 2 - √3 ] /2
= 2 - √3 .
We see that, L. H. S = R. H. S = 2 - √3 .
Hence proved that, 1 - sin60°/cos60° = tan60°-1/tan60° + 1
We know that,
sin60 = √3/2
cos60 = 1/2
tan60 = √3
Now,
Finding the value of L. H. S,
1 - sin60/ ( cos60 )
=[ 1 - √3/2 ] / 1/2
= [ 2 - √3 / 2 ] * 2
= 2 - √3
Now, Finding Value of R. H. S,
tan60 - 1 / tan60 + 1
= √3 - 1 / √3 + 1 [ Rationalise denominator ]
= (√3 - 1 )² / 2
= 3 + 1 - 2√3 /2
= 4 - 2√3 /2
= 2 [ 2 - √3 ] /2
= 2 - √3 .
We see that, L. H. S = R. H. S = 2 - √3 .
Hence proved that, 1 - sin60°/cos60° = tan60°-1/tan60° + 1
Answered by
7
HELLO DEAR,
we know that:-
sin60° = √3/2
cos60° = 1/2
tan60° = √3
NOW,
[1 - sin60°]/cos60°
= [1 - (√3/2) ]/ (1/2)
= [ ( 2 - √3)/2] / (1/2)
= (2 - √3) (R.H.S)
(tan60° - 1) / (tan60° + 1)
= (√3 - 1) / (√3 + 1)
= (√3 - 1) / (√3 + 1) × (√3 - 1)/(√3 - 1)
= (3 + 1 - 2√3)/ (3 - 1)
= (4 - 2√3)/2
= 2(2 - √3)/2
= (2 - √3) ( L.H.S)
HENCE,
R.H.S = L.H.S
I HOPE ITS HELP YOU DEAR,
THANKS
we know that:-
sin60° = √3/2
cos60° = 1/2
tan60° = √3
NOW,
[1 - sin60°]/cos60°
= [1 - (√3/2) ]/ (1/2)
= [ ( 2 - √3)/2] / (1/2)
= (2 - √3) (R.H.S)
(tan60° - 1) / (tan60° + 1)
= (√3 - 1) / (√3 + 1)
= (√3 - 1) / (√3 + 1) × (√3 - 1)/(√3 - 1)
= (3 + 1 - 2√3)/ (3 - 1)
= (4 - 2√3)/2
= 2(2 - √3)/2
= (2 - √3) ( L.H.S)
HENCE,
R.H.S = L.H.S
I HOPE ITS HELP YOU DEAR,
THANKS
Similar questions